Violência obstétrica em julgamento: etnografia de acórdãos sobre um conceito em disputa - Ana Clara Matias Brasileiro (2023)
Although there is no consensus in Brazil on the concept of obstetric violence, the evidence indicates that it does occur, with one in four women reporting having suffered some form of violence from the team assisting them during pregnancy, childbirth and the postpartum period. Despite this, there are relatively few judgments in which it is found. This research aims to investigate the treatment given by the Brazilian judiciary to cases involving obstetric violence, to identify and analyze the types of claims that, when judged, give rise to the use of the expression and, finally, to verify whether there is any tendency to recognize or not the duty to compensate damages due to the practice of obstetric violence. Therefore, theoretical research was carried out to discuss the clash between models of childbirth care, the unveiling of obstetric violence, based on the idea of moral insult, and the fight against this form of violence, with communication strategies that locate it as a public problem, as a contemporary chapter in the fight for women's human rights. The methodology of ethnography of documents was then adopted, carrying out quantitative research and panoramic analysis of the set of judgments, in the foreground, qualitative and quantitative analysis of the judgments judged by the TJMG and qualitative analysis of emblematic cases for the field with a focus on the argumentation and treatment given to obstetric violence in each case. Considering the understandings and disputes on the subject, it was possible to see that the clash between the technicist and humanized models of care has made it possible to question protocol practices, which are commonplace and naturalized, in obstetrics practiced with the hospitalization of childbirth. These new demands, which have reached the Brazilian courts, have received diffuse treatment, and it was not possible to identify a stabilized conceptual understanding in the corpus analyzed. There is, however, a more frequent, albeit still timid, use of the term, which is part of the process of expanding rights.